Cake filtration at high biomass nitrogen removing systems - Özdemir, Burcu. (Thesis (Ph.D.)-Bogazici University. Institute of Environmental Sciences, 2013., 2013)
Pilot scale cake filtration biological reactor (CFBR) and membrane bioreactor (MBR) were operated (capacity: 100 m3/d) for 26 months. The system was evaluated according to conventional cake filtration theory using its plots of V vs. t and t/V vs. V. Standard blocking model plots of CFBR were compatible (R2> 0.95) for the initial period; the latter was best fitted to the cake filtration model (R2> 0.99). The linearity between t/V and V was observed individually, showing a change of filtration characteristics at the transition point. Results of a particular period (six months) with complete sludge retention were presented to state the sludge production pattern and, the activity and diversity of nitrogen converters. The average sludge yield reached equilibrium after day 105 (0.25 kgMLSS/kgCOD, MLSS~15,000 mg/L). Volatile portion of mixed liquor suspended solids (MLVSS/MLSS) increased– decreased–increased and stabilized around 0.57. Inert material stabilization showed that inerts could be degraded at sufficiently long SRTs. The nitrifier population was adversely affected by gradually increased biomass with insignificant effluent quality change. However, coexistence of aerobic and anaerobic ammonia oxidizers in a partially aerated system was confirmed. The total operation cost of such high biomass filtration system could be 9–15 percent less than that of a biological nutrient removal (BNR) plant because of the decreased expenses for sludge disposal.
Keywords: Active nitrogen.